Conference Record of the Twenty Fifth IEEE Photovoltaic Specialists Conference - 1996 1996
DOI: 10.1109/pvsc.1996.564216
|View full text |Cite
|
Sign up to set email alerts
|

Initial results for the silicon monolithically interconnected solar cell product

Abstract: This technology is based on AstroPower's electrostatic bonding and silicon solar cell processing techniques. Electrostatic bonding allows silicon wafers to be permanently attached to a thermally matched glass superstrate and processed to form the monolithically interconnected devices. These devices can be tailored for space and terrestrial applications. The costs of the monolithic interconnection compare favorably to labor intensive, conventionally strung solar cell arrays. Voltage and current outputs can be v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…23 Standard measurements of photovoltaic devices involve current-voltage characteristics measured under standard solar spectrum AM1Á5, 100 mW/cm 2 , 25 C. Photovoltaic minimodules fabricated by the two approaches described above have been systematically measured under standard conditions. Samples fabricated by adhesive bonding were 16 The main photovoltaic parameters measured for the different samples of the two different design approaches (glass/adhesive and silicon/fusion) are summarized in Table I. Where V oc is the open circuit voltage, I sc the short-circuit current, P m is the maximum delivered power by the array, FF the fill factor, and the photovoltaic conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Standard measurements of photovoltaic devices involve current-voltage characteristics measured under standard solar spectrum AM1Á5, 100 mW/cm 2 , 25 C. Photovoltaic minimodules fabricated by the two approaches described above have been systematically measured under standard conditions. Samples fabricated by adhesive bonding were 16 The main photovoltaic parameters measured for the different samples of the two different design approaches (glass/adhesive and silicon/fusion) are summarized in Table I. Where V oc is the open circuit voltage, I sc the short-circuit current, P m is the maximum delivered power by the array, FF the fill factor, and the photovoltaic conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches have been followed to isolate individual cells from one another: trench isolation with anisotropic etching of silicon, 16 V-groove, 17 wafer through-holes, 11 to interconnect them in series: wire bonding, 11 metal photolithography, 16 etc. Moreover, handling or substrate material has been reported for glass 16,17 and semiinsulated semiconductors, 9 or silicon dioxide in SOI wafers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar ideas were proposed by Moddel [29], Sinton [30] and Kurt [31] in 1986, 1992 and 1995 respectively. Moreover, the Company AstroPower Inc. presented from 1993 to 2003 [32][33][34] results of MIMs for space power applications by using a design with similar characteristics to that of Warner [21], Chapell [28] and , which demonstrated experimental efficiencies of 11.1% at 1-sun illumination [33]. In 2003, Peters et al [35] presented efficiencies of 11% for MIM devices on SOI substrates using the aforementioned groove-like isolation.…”
Section: Si-based Mimsmentioning
confidence: 99%
“…In , a comparison of these technologies is analysed; from and , it can be concluded that PV energy sources can fulfil a broad power range, keeping a high power density ratio compared with other alternatives. There are some alternatives of mini‐PV generators: silicon‐based , GaAs‐based and others, for example in that based on CuInS 2 . Excluding concentration applications , most of the state‐of‐the‐art alternatives exhibit higher areas than the mini‐PV generators reported in this work.…”
Section: Introductionmentioning
confidence: 99%